Ultimate Bearing Capacity of Ring Foundations Embedded in Undrained Homogeneous Clay. (13th July 2022) - Wang, An-hui; Zhang, Yan-fang; Xia, Fan; Luo, Ru-ping; Wang, Ning
Abstract : A ring foundation is widely used in bridges, water towers, caissons, and other engineering structures, and its ultimate bearing capacity is one of the significant concerns in engineering design. This paper is aimed at exploring the ultimate bearing capacity of ring foundations embedded in undrained clay. Based on the finite element limit analysis, effects of the inside-to-outside radius ratio, embedment depth ratio, cutting face inclination angle, and face roughness on the vertical ultimate bearing capacity of ring foundations are investigated. The results show that the ultimate bearing capacity of the ring foundation increases gradually with the embedment depth ratio. When the embedment depth ratio D / B reaches a critical value, the bearing capacity tends to be stable, and the critical embedment depth ratio is affected by the inside-to-outside radius ratio of the ring foundation, varying from 0.2 to 0.4. The ultimate bearing capacity of the ring foundation decreases with cutting face inclination angle β . When β ≤ 40 °, the ultimate bearing capacity tends to be stable, and the bearing capacity is reduced by approximately 30%. The influence of the cutting face inclination angle on the bearing capacity is highly dependent on the roughness of the cutting face.